Aspects of the presence of the Aristotelian Logic in Western Christianity and Eastern Christianity:: The “middle places” according to Boethius and Holobolus - Terezis, Christos (Dia-noesis: A Journal of Philosophy, 2024)
In this article, we discuss a particular aspect of the presence of the Aristotelian Logic –mainly based on the treatise Topics– in the Christianity of the West as well as in the Christianity of the East, with Boethius and Manuel Holobolus as representatives. As a reference text, we have Boethius’ treatise De topicis differentiis, which was translated into Greek, with certain adaptations and individual comments, by Manuel Holobolus. We approach a concise passage from the Byzantine scholar’s translation, which refers to “middle places”, that is to say, to those which arise neither from the meaning of names per se nor from external factors alone, but from their encounter with each other under particular circumstances. We investigate how “middle places” are distinguished into three categories –a) by πτώσις (case), b) by συστοιχία (co-ordination), and c) by διαίρεσις (division)– and how arguments are structured on the basis of their use. They appear as modalities of nouns, mainly through adjectives and adverbs within prepositional phrases, which do not refer to semantic singulars but to a structure of various kinds of relations between situations and between persons, with evaluative schemes sometimes present. We pay particular attention to how an actual case highlights both morphological and semantic variations so that it is not just a grammatical scheme but also one of philosophical interest. We indicate how through the “middle places” formal Logic is brought into relevance with Ontology, or nominal reflections with pragmatological data, in the perspective of what can be called conceptual realism, which refers to how a meaning adapts to the external conditions it is asked to describe and is transformed accordingly. Finally, we conclude that through Boethius’ original text and Holobolus's translation, the Aristotelian formal Logic is utilized by the theological and philosophical atmosphere of Christianity, both in the West and in the East, even though there is a gap of about eight centuries between the two thinkers.